The impact of metacognitive changes of digitalized consciousness on public administration policy: El impacto de los cambios metacognitivos de la conciencia digitalizada en la política de la administración pública - Lepskyi, Maksym; Kudinov, Igor; Lepska , Natalia; Rusetsky, Alexander (Political Questions, 2023)
Using the method of observation and analysis of official documents, the article explores the influence of the digital creative class on traditional state institutions, which ultimately leads to metacognitive changes in the digitized consciousness of society. Currently, state institutions face challenges in the digital age, such as the «information bubble,» irrational and emotional user choices, and competition for attention based on impressions, «likes,» and diverse opinions. Artificial intelligence technologies have influenced various industries and public administration, causing a shift from traditional interaction to virtual formats with state institutions. An example of this transformation is the Ukrainian online service DIIA, which offers document circulation, access to open records, identification and identity confirmation, and data tracking and analysis systems. It is concluded that, the interaction between public administration and digitization processes falls into four main categories: as a prototype of complement, reinforcement of the «exoskeleton», connection and blending of solutions in human-AI interaction, and delegation or replacement of human decision-making by AI.